Physical workload and bodily fatigue after work: cross-sectional study among 5000 workers. - Bláfoss, Rúni; Sundstrup, Emil; Jakobsen, Markus D; Brandt, Mikkel; Bay, Hans; Andersen, Lars L (European Journal of Public Health, 2019)
Background Persistent bodily fatigue after working days may indicate an imbalance between work demands and capacity of the workers. This study aimed to investigate associations between physical exposures at work and bodily fatigue after work. Methods Danish workers with physical work (N =5377) answered questions about various physical exposures during work and bodily fatigue after work in the 2010 round of the Danish Work Environment Cohort Study. Associations were modeled using binary logistic regression controlled for various confounders. Results Mean age among the younger (<50 years) and older (≥50 years) workers was 36 and 56 years, respectively. Younger and older workers exposed to various physical exposures (e.g. 'bending/twisting the back') for more than a quarter of the workday were more fatigued after work. An exposure–response relationship was observed between the number of physical exposures and bodily fatigue, with odds ratios (OR) for fatigue in the body among younger workers being 1.01 (95%CI 0.63–1.63), 1.59 (95%CI 1.01–2.50), 2.37 (95%CI 1.54–3.66) and 2.84 (95%CI 1.85–5.36) for 1, 2, 3 and ≥4 types of combined physical exposures, respectively. Correspondingly, for older workers, ORs were 1.95 (95%CI 1.09–3.51), 4.06 (95%CI 2.32–7.12), 4.10 (95%CI 2.28–7.37) and 4.90 (95%CI 2.72–8.82) for 1, 2, 3 and ≥4 exposures, respectively. Conclusion While some of the single factor exposures were associated with increased bodily fatigue, the most marked associations were found when summing the number of different exposures. These results indicate that workplaces should focus on the sum of combined physical exposures rather than focusing solely on single exposures.